Successful steroid treatment of coma induced by severe spontaneous intracranial hypotension - Goto, Shunsaku (Nagoya J Med Sci, 2016)
Spontaneous intracranial hypotension (SIH) is a syndrome characterized by low cerebrospinal fluid (CSF) pressure and postural headaches. It is a rare condition which may sometimes present with severe symptoms such as stupor or coma. The standard treatment protocol includes conservative measures such as bed rest, hydration, and steroids. However, severe cases may require invasive measures such as epidural blood patch (EBP), continuous epidural saline infusion, epidural fibrin glue, or surgical repair of the dural defect. In this report, we describe a case of severe SIH resulting in coma that exhibited dramatic improvement on intravenous administration of steroids. This is the first report of severe SIH causing coma that was treated non-invasively by steroids only.